Global methane and nitrous oxide emissions from inland waters and estuaries. (27th May 2022) - Zheng, Yajing; Wu, Shuang; Xiao, Shuqi; Yu, Kai; Fang, Xiantao; Xia, Longlong; Wang, Jinyang; Liu, Shuwei; Freeman, Chris; Zou, Jianwen
Abstract: Inland waters (rivers, reservoirs, lakes, ponds, streams) and estuaries are significant emitters of methane (CH4 ) and nitrous oxide (N2 O) to the atmosphere, while global estimates of these emissions have been hampered due to the lack of a worldwide comprehensive data set of CH4 and N2 O flux components. Here, we synthesize 2997 in‐situ flux or concentration measurements of CH4 and N2 O from 277 peer‐reviewed publications to estimate global CH4 and N2 O emissions from inland waters and estuaries. Inland waters including rivers, reservoirs, lakes, and streams together release 95.18 Tg CH4 year −1 (ebullition plus diffusion) and 1.48 Tg N2 O year −1 (diffusion) to the atmosphere, yielding an overall CO2 ‐equivalent emission total of 3.06 Pg CO2 year −1 . The estimate of CH4 and N2 O emissions represents roughly 60% of CO2 emissions (5.13 Pg CO2 year −1 ) from these four inland aquatic systems, among which lakes act as the largest emitter for both CH4 and N2 O. Ebullition showed as a dominant flux component of CH4, contributing up to 62%–84% of total CH4 fluxes across all inland waters. Chamber‐derived CH4 emission rates are significantly greater than those determined by diffusion model‐based methods for commonly capturing of both diffusive and ebullitive fluxes. Water dissolved oxygen (DO) showed as a dominant factor among all variables to influence both CH4 (diffusive and ebullitive) and N2 O fluxes from inland waters. Our study reveals a major oversight in regional and global CH4 budgets from inland waters, caused by neglecting the dominant role of ebullition pathways in those emissions. The estimated indirect N2 O EF5 values suggest that a downward refinement is required in current IPCC default EF5 values for inland waters and estuaries. Our findings further indicate that a comprehensive understanding of the magnitude and patterns of CH4 and N2 O emissions from inland waters and estuaries is essential in defining the way of how these aquatic systems will shape our climate. Abstract : Inland waters (rivers, reservoirs, lakes, ponds, streams) and estuaries are significant emitters of methane (CH4 ) and nitrous oxide (N2 O) to the atmosphere, while global estimates of these emissions have been hampered due to the lack of a worldwide comprehensive data set of CH4 and N2 O flux components. Here, we synthesize 2997 in‐situ flux or concentration measurements of CH4 and N2 O from 277 peer‐reviewed publications to estimate global CH4 and N2 O emissions from inland waters and estuaries.